BOARDING TIME AND PATIENT SATISFACTION AT THE EMERGENCY DEPARTMENT - Uswatun Hasanah; Nurul Jannatul Firdausi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Delays of inpatient transfer from the Emergency Department (ED) will affect delayed care, overcrowd at ED, and patient’s disappointment. Such patient transfer delay from the Emergency Departement (ED) also occurs at Haji General Hospital, Surabaya.Aims: This study analyzed the relationship  between inpatient boarding time from Emergency Departement (ED) and patient satisfaction at Haji General Hospital, Surabaya.Methods: This was an observational research using a cross-sectional approach. The population was 980 ED patients who decided to be hospitalized. Out of 980 ED patients, the study only involved 83 respondents selected by simple random sampling. The instruments used were observational sheet and questionnaires to collect data which were then analyzed with a chi-square test.Results: Average boarding time was 142 minutes 25 seconds (minimum = 60 minutes; maximum = 290 minutes). Almost all respondents (81.3%) were satisfied about fast boarding time. Inpatient boarding time at the Emergency Departement (ED) was significantly related to patient satisfaction (p = 0.058 <α = 0.1). The faster inpatients move to ED, the more satisfied they are.Conclusion: The average patient boarding time from the Emergency Departement (ED) to Inpatient Unit was slow. Respondents were satisfied with the quality of services even though patient boarding time was slow. The hospital should pay more attention to evaluate the minimal standard of boarding time, ensure the availability of beds,  and improve the quality of facilities and services to enhance patient satisfaction. Keywords: Boarding time, Emergency Department, Inpatient, Satisfaction.